The Influence of Work Motivation and Mentality on Human Resource Education Performance - Fahriansyah Fahriansyah; Nur Afifah; Mustaruddin Mustaruddin; Romi Siswanto; Achmad Anwar Abidin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the influence of work motivation and mentality on the performance of human resources (HR) Education at the Open University Service Center (SALUT), Pontianak. The research method used a quantitative approach with a survey of 71 SALUT employees. Data were analyzed using multiple linear regression and Structural Equation Modeling (SEM). The results of the study showed that work motivation had a significant negative effect on human resource performance, while mentality had a significant positive influence. The determination coefficient of 63.2% indicates that both variables simultaneously affect employee performance. These findings affirm the importance of developing a growth mentality or mindset in improving the quality of services at SALUT. This study provides recommendations for management to focus on forming a positive mentality to support the improvement of human resource performance